Environmental Quality, Corruption and Industry Growth: The Global Perspective - Cui, Min; Wang, Jun-Sheng; Chang, Chun-Ping (Problemy Ekorozwoju, 2021)
This paper investigates the causal relationship between environmental quality and corruption for 129 countries, using the panel cointegration and panel-based error correction models for the period 2002-2015. In the paper, we use EPI, EHI, and EVI to represent environmental quality, which are more reasonable and comprehensive. We further take industry growth into consideration and investigate its impact on environmental quality. Our results corroborate that there exists a long-term equilibrium cointegrated relationship among the variables, both of corruption and industry growth have a negative effect on environmental quality and the corruption can seriously decrease environmental quality in the long term, while industry growth weakens environmental quality no matter in the short or long run.